Regionalização de vazões na bacia hidrográfica do Rio Piquiri - Araujo, Fernanda Cristina (2015)
The objective of this research was to regionalize the minimum seven-day flows, annual average long-term duration, maximum and permanence flows of 90 and 95% of the catchment area of the Piquiri River - PR. The peak flows were regionalized associated with a specific return period (2, 5, 10, 25, 50 and 100 years) and the minimum flow lasting seven days was associated with a 10-year return period. To represent the series of maximum and minimum flows probability Pearson type III distributions, two- and three-parameter Log-normal and type III Log-Pearson, Gumbel (for maximum flows) and Weibull (for minimum flows only) were used. Type III Log-Pearson distribution obtained in 100% of cases, the lowest standard error, presenting the best adjustment with the minimum flow data. About 70% of the data stations showed the lowest standard error when adjusted to this three- parameter log-normal distribution. Thus, the three-parameter Log-Normal distribution was adopted as default, but stations 64765000 (Porto Paiquerê), 64771500 (Porto Guarani), 64785000 (Goio Bang Bridge), which did not obtain adjustment with this distribution, used the two-parameter Log-Normal distribution. The period average flow, once it is characterized as the average of the annual average flow, was regionalized without considering the risk level. In order to obtain the permanence curve, the procedure based on obtaining the frequency classes was carried out. In the regionalization procedure the following methods were employed: the traditional method described by Eletrobrás (1985a), the linear interpolation method (ELETROBRÁS, 1985b), the method proposed by Chaves et al. (2002), the modified linear interpolation and the modified Chaves (NOVAES et al., 2007). As explanatory variables for the traditional method, the following physical characteristics were used: drainage area; the length of the main river; the basin mean land slope; the mean land slope of the main river; drainage density, and climatic characteristics: the total annual rainfall; the precipitation of the wettest quarter; the precipitation of the driest quarter. The regression models that best fit the flow data are the simple potential and the multiple potential ones. The area and the density drainage are the best explanatory variables for the estimate the minimum seven-day flow and ten-year return period (Q7,10). The length of the main river is the best explanatory variable for the estimate of flow rates of 90 and 95% of permanence (Q90 and Q95, respectively). The area and the drainage density are the best explanatory variables to estimate the minimum seven-day flow and the ten-year return period of (Q7,10), the length of the main river and the area for the flow estimate with 90 and 95% of permanence (Q90 and Q95, respectively) and the length of the main river is the best explanatory variable for the estimate of maximum flows considering all return periods studied. The method of linear interpolation produces similar estimates to the ones obtained with the Conventional method and can be used in situations, especially when there is sufficient information for adjustment of the regression models. Estimates of minimum flows (Q7,10, Q90 and Q95) and of average flow (Qmed), performed by using the Chaves method are similar to the ones obtained with the Conventional method , while the estimates of peak flows for all return periods studied, presented major errors. The modified methods did not promote significant improvement of the estimates compared to the original methods.